11th NCERT/CBSE Sequences and series Exercise 9.1 Questions 14
Hi

### Write the first five terms of each of the sequences in Exercise 1 to 6 whose nth terms are

Question (1)

an = n(n+2)

Solution

an = n(n+2)
Substituting n = 1, 2, 3, 4, and 5, we obtain a1 = 1(1+2)=3
a2 = 2(2+2)=8
a3 = 3(3+2)=15
a4 = 4(4+2)=24
a5 = 5(5+2)=35
Therefore, the required terms are 3, 8, 15, 24, and 35.

Question (2)

${a_n} = \frac{n}{{n + 1}}$

Solution

${a_n} = \frac{n}{{n + 1}}$
Substituting n = 1, 2, 3, 4, 5, we obtain ${a_1} = \frac{1}{{1 + 1}} = \frac{1}{2}$ ${a_2} = \frac{2}{{2 + 1}} = \frac{2}{3}$ ${a_3} = \frac{3}{{3 + 1}} = \frac{3}{4}$ ${a_4} = \frac{4}{{4 + 1}} = \frac{4}{5}$ ${a_5} = \frac{5}{{5 + 1}} = \frac{5}{6}$ Therefore, the required terms are $\frac{1}{2},\frac{2}{3},\frac{3}{4},\frac{4}{5}\;and \;\frac{5}{6}$

Question (3)

an = 2n

Solution

an = 2n
Substituting n = 1, 2, 3, 4, 5, we obtain
a1 = 21=2
a2 = 22=4
a3 = 23=8
a4 = 24=16
a5 = 25=32

Question (4)

${a_n} = \frac{{2n - 3}}{6}$

Solution

${a_n} = \frac{{2n - 3}}{6}$
Substituting n = 1, 2, 3, 4, 5, we obtain ${a_1} = \frac{{2 \times 1 - 3}}{6} = \frac{{ - 1}}{6}$ ${a_2} = \frac{{2 \times 2 - 3}}{6} = \frac{1}{6}$ ${a_3} = \frac{{2 \times 3 - 3}}{6} = \frac{3}{6} = \frac{1}{2}$ ${a_4} = \frac{{2 \times 4 - 3}}{6} = \frac{5}{6}$ ${a_5} = \frac{{2 \times 5 - 3}}{6} = \frac{7}{6}$ Therefore, the required terms are $\frac{{ - 1}}{6},\frac{1}{6},\frac{1}{2},\frac{5}{6}and\frac{7}{6}$

Question (5)

an = (-1)n-1 5n+1

Solution

Substituting n = 1, 2, 3, 4, 5, we obtain
a1 = (-1)1-1 51+1=52 = 25
a2 = (-1)2-1 52+1= -53 = -125
a3 = (-1)3-1 53+1=54 = 625
a4 = (-1)4-1 54+1=-55 = -3125
a5 = (-1)4-1 55+1=56 = 15625
Therefore, the required terms are 25, –125, 625, –3125, and 15625.

Question (6)

${a_n} = n\frac{{{n^2} + 5}}{4}$

Solution

Substituting n = 1, 2, 3, 4, 5, we obtain
${a_1} = 1\times\frac{{{1^2} + 5}}{4} = \frac{6}{4} = \frac{3}{2}$ ${a_2} = 2 \times \frac{{{2^2} + 5}}{4} = 2 \times \frac{9}{4} = \frac{9}{2}$ ${a_3} = 3 \times \frac{{{3^2} + 5}}{4} = 3 \times \frac{{14}}{4} = \frac{{21}}{2}$ ${a_4} = 4 \times \frac{{{4^2} + 5}}{4} = 4 \times \frac{{21}}{4} = 21$ ${a_5} = 5 \times \frac{{{5^2} + 5}}{4} = 5 \times \frac{{30}}{4} = \frac{{75}}{2}$ Therefore, the required terms are $\frac{3}{2},\frac{9}{2}.\frac{{21}}{2},21, \; and \;\frac{{75}}{2}$

### Find the indicated terms in each of the sequences in Exercise 7 to 10 whose nth terms are

Question (7)

an = 4n -3; a17, a24

Solution

Substituting n = 17, we obtain
a17 = 4(17) -3 =68-3=65
Substituting n = 24, we obtain
a24 = 4(24) -3 = 96-3 =93

Question (8)

${a_n} = \frac{{{n^2}}}{{{2^n}}};{a_7}$

Solution

Substituting n = 7, we obtain ${a_7} = \frac{{{7^2}}}{{2^ 7}} = \frac{49}{128}$

Question (9)

an = (-1)n-1 n3; a9

Solution

Substituting n = 9, we obtain
a9 = (-1)9-1 (9)3 = (9)3 = 729

Question (10)

${a_n} = \frac{{n\left( {n - 2} \right)}}{{n + 3}};{a_{20}}$

Solution

Substituting n = 20, we obtain ${a_{20}} = \frac{{20\left( {20 - 2} \right)}}{{20 + 3}} = \frac{{20\left( {18} \right)}}{{23}} = \frac{{360}}{{23}}$

### Write the first five terms of each of the dequences in Exercise 11 to 13 and obtain the corresponding series:

Question (11)

a1 =3, an = 3an-1 + 2 for all n >1

Solution

a1 =3, an = 3an-1 + 2 for all n >1
⇒ a2=3a1 +2 = 3(3) +2 =11
a3 = 3a2 +2 = 3(11) +2 = 35
a4 = 3a3+2 = 3(35) +2 = 107
a5 = 3a4+2 = 3(17) +2 = 323
Hence, the first five terms of the sequence are 3, 11, 35, 107, and 323.
The corresponding series is 3 + 11 + 35 + 107 + 323 + …

Question (12)

${a_1} = - 1,{a_n} = \frac{{{a_{n - 1}}}}{n},n \ge 2$

Solution

${a_1} = - 1,{a_n} = \frac{{{a_{n - 1}}}}{n},n \ge 2$ $\Rightarrow {a_2} = \frac{{{a_1}}}{2} = \frac{{ - 1}}{2}$ ${a_3} = \frac{{{a_2}}}{3} = \frac{{ - 1}}{6}$ ${a_4} = \frac{{{a_3}}}{4} = \frac{{ - 1}}{{24}}$ ${a_5} = \frac{{{a_4}}}{5} = \frac{{ - 1}}{{120}}$ Hence, the first five terms of the sequence are $- 1,\frac{{ - 1}}{2},\frac{{ - 1}}{6},\frac{{ - 1}}{{24}} \; and \; \frac{{ - 1}}{{120}}$ The corresponding series is $\left( { - 1} \right) + \left( {\frac{{ - 1}}{2}} \right) + \left( {\frac{{ - 1}}{6}} \right) + \left( {\frac{{ - 1}}{{24}}} \right) + \left( {\frac{{ - 1}}{{120}}} \right) + ...$

Question (13)

a1 = a2 = 2, an = an-1 -1, n > 2

Solution

a1 = a2 = 2, an = an-1 -1, n > 2
⇒ a3 = a2 - 1 = 2 - 1 = 1
a4 = a3 - 1 = 1 - 1 = 0
a5 = a5 - 1 = 0 - 1 = -1
Hence, the first five terms of the sequence are 2, 2, 1, 0, and –1.
The corresponding series is 2 + 2 + 1 + 0 + (–1) + …

Question (14)

The Fibonacci sequence is defind by
1 = a1 = a2 and an = an-1 + an-2, n > 2
Find $\frac{{{a_{n + 1}}}}{{{a_n}}}$, for n=1, 2, 3, 4, 5

Solution

1 = a1 = a2
an = an-1 + an-2 , n> 2
∴ a3 = a2 + a1 = 1 + 1 =2
a4 = a3 + a2 = 2 + 1 =3
a5 = a4 + a3 = 3 + 2 =5
a6 = a5 + a4 = 5 + 3 =8
$\therefore \;For\;n = 1,\frac{{{a_{n + 1}}}}{{{a_n}}} = \frac{{{a_2}}}{{{a_1}}} = \frac{1}{1} = 1$ $\therefore \;For\;n = 2,\frac{{{a_{n + 1}}}}{{{a_n}}} = \frac{{{a_3}}}{{{a_2}}} = \frac{2}{1} = 2$ $For\;n = 3,\frac{{{a_{n + 1}}}}{{{a_n}}} = \frac{{{a_4}}}{{{a_3}}} = \frac{3}{2}$ $\therefore \;For\;n = 4,\frac{{{a_{n + 1}}}}{{{a_n}}} = \frac{{{a_5}}}{{{a_4}}} = \frac{5}{3}$ $\therefore \;For\;n = 5,\frac{{{a_{n + 1}}}}{{{a_n}}} = \frac{{{a_6}}}{{{a_5}}} = \frac{8}{5}$